2020
DOI: 10.1186/s13049-020-00742-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the relative importance of predictors of survival in out of hospital cardiac arrest: a machine learning study

Abstract: Introduction Studies examining the factors linked to survival after out of hospital cardiac arrest (OHCA) have either aimed to describe the characteristics and outcomes of OHCA in different parts of the world, or focused on certain factors and whether they were associated with survival. Unfortunately, this approach does not measure how strong each factor is in predicting survival after OHCA. Aim To investigate the relative importance of 16 well-recognized factors in OHCA at the time point of ambulance arrival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 36 publications
5
41
0
5
Order By: Relevance
“…Two studies reported the use of AI as a deep-learning-based prognostic system and a machine-learning algorithm to discover potential factor influencing outcomes and predict neurological recovery and discharge alive from hospital. 130,131 Further research is needed to understand the potential of this new AI technology as a tool to support human clinical decisions.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Two studies reported the use of AI as a deep-learning-based prognostic system and a machine-learning algorithm to discover potential factor influencing outcomes and predict neurological recovery and discharge alive from hospital. 130,131 Further research is needed to understand the potential of this new AI technology as a tool to support human clinical decisions.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…A recent study using machine learning confirmed that the most important predictor of OHCA survival was the presence of an initial shockable rhythm, followed by age, time to the initiation of CPR, EMS response time and the place of cardiac arrest. 30 In particular, among patients found with a shockable rhythm, the five most important predictors were the time to defibrillation, age, defibrillation (yes/no), place of cardiac arrest, and time from cardiac arrest to the initiation of CPR. In our study, although the COVID-19 group had a higher incidence of an initial shockable rhythm than the pre-COVID-19 group, they were older and had fewer cases of cardiac arrest in public places, fewer cases of bystander CPR and AED use, and delayed EMS response time.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches leverage ML's ability to model non-linear relationships and interactions in data with a very large number of variables, then use explainability techniques extract novel hypotheses that can be tested further. [34][35][36] Local explainability aims to provide insight about why a model made a specific prediction, and it has been identified by clinicians as critical in the context of using a model's outputs to inform clinical practice. 16 Local explanations can be incorporated directly into clinical decision support tools in electronic health records in order to enhance the transparency and the actionability of predictions.…”
Section: Key Concepts In Explainable Machine Learningmentioning
confidence: 99%